Progression of Heart Failure in People with Type 2 Diabetes in Germany: An Analysis Using German Health Insurance Claims Data - Keni Cheng-Siang Lee; Tobias Wagner; Adee Kennedy; Michael Wilke (Journal of Health Economics and Outcomes Research)
**Background:** Individuals with type 2 diabetes (T2D) show high risk of heart failure (HF). Left ventricular ejection fraction is a major factor for disease progression. In Germany, no recent longitudinal data are available. **Objectives:** To (1) measure the proportion of individuals with T2D who acquire HF over 2 years and (2) categorize ejection fraction using routine data and an algorithm, and (3) understand progression of HF in 5-year follow-up. **Methods:** This descriptive, retrospective study used longitudinal data from German statutory health insurance claims. A model using coded data classified the patients with HF into ejection fraction (EF) categories. Individuals were selected during 2013, with an inclusion period from 2014 to 2015 and a follow-up from 2016 to 2020. Baseline characteristics included demographic data, disease stage, comorbidities, and risk factors. Follow-up criteria included major adverse cardiac events (MACEs), EF category, and mortality. Disease progression was visualized by Sankey plots. **Results:** Among the 173 195 individuals with T2D identified in 2013, 6725 (median age, 74 years) developed HF in 2014 or 2015. 34.4% of individuals had MACEs, and 42.9% died over 5 years. Myocardial infarction (42%) was the most common event, followed by stroke (32%) and hospitalization (28%). A total of 5282 (78.54%) patients were classified into preserved EF and 1443 (21.46%) into reduced EF. Survival after 5 years was 71% in HF for preserved EF patients, and 29% in the HF for those with reduced EF. **Conclusion:** Heart failure is relevant in individuals with diabetes. A high number of patients may likely not survive a 5-year period. Validation of the model with German data is highly desirable. New ways of close monitoring could help improve outcomes.